Who is too old for epicardial fat volume quantification?. (25th November 2020) - Brizido, C; Matos, D; Ferreira, A.M; Sousa, J.A; Freitas, P; Presume, J; Rodrigues, G.R; Carmo, J; Costa, F.M; Carmo, P; Cavaco, D; Morgado, F.B; et al.
Abstract: Introduction: Epicardial adipose tissue has been implicated in the pathophysiology of atrial fibrillation (AF) and was recently shown to be an independent predictor of AF relapse rate and severity after pulmonary vein isolation (PVI). However, its impact in older patients hasn't been analyzed. The aim of this study was to assess the relative importance of pericardial fat in an older population of patients undergoing pulmonary vein isolation (PVI). Methods: Single-center retrospective study of symptomatic drug-resistant AF patients undergoing PVI from November/2015 to June/2019. Baseline demographics, clinical and imaging data including cardiac CT and clinical outcomes were collected and analyzed. Population was dichotomized according to age above or below 70 years of age and groups were compared. Epicardial fat volume was quantified by contrast-enhanced cardiac CT using a semi-automated method. The study endpoint was symptomatic and/or documented AF recurrence after a 3-month blanking period. Results: We assessed 575 patients (354 males, mean age 61±11 years, 449 paroxysmal AF), 145 of which were 70 or older. Compared to the younger cohort, these patients had an higher prevalence of women, lower BMI (27 kg/m 2 [IQR 24–30] vs 28 kg/m 2 [IQR 25–30] kg/m 2, p=0.012), higher CHA2DS2-VASc score (3 [IQR 2–4] vs 1 [IQR 1–2], p<0.001) and larger indexed left atrial volumes (61mL [IQR 52–84] vs 54mL [IQR 47–66], p<0.001). Median epicardial fat volume was 2.96 cm 3 /m 2 [IQR 2.99–4.00] in the overall population and was higher in older patients (HR 2.21 cm 3 /m 2 [IQR 1.44–3.17] vs HR 1.87 cm 3 /m 2 [IQR 1.24–2.90]; p=0.016). During follow-up, 232 patients relapsed (40%), with similar recurrence rates between younger and older patients (40% vs 42%, p=0.63) according to Kaplan-Meier survival curve analysis (HR 1.10, 95% CI 0.82–1.48; log-rank p=0.519). Epicardial fat volume remained an independent predictor of AF relapse in the older subset of patients (HR 1.06 for every 1 cm 3 /m 2 increase in epicardial fat volume [95% CI 1.28–2.00]; p<0.001), as did the presence of non-paroxysmal AF (HR 2.78 [95% CI 1.48–5.21]; p=0.001). Conclusion: Patients over 70 years old with drug-refractory symptomatic AF presented with higher epicardial fat volume. Epicardial fat burden showed similar predictive power for AF relapse after PVI in this subset of patients, representing a useful tool for intervention decision across this age spectrum. Funding Acknowledgement: Type of funding source: None